The light we carry overcoming in uncertain times - Obama, Michelle (New York Random House, 2023)
There may be no tidy solutions or pithy answers to life?s big challenges, but Michelle Obama believes that we can all locate and lean on a set of tools to help us better navigate change and remain steady within flux. In The Light We Carry, she opens a frank and honest dialogue with readers, considering the questions many of us wrestle with: How do we build enduring and honest relationships? How can we discover strength and community inside our differences? What tools do we use to address feelings of self-doubt or helplessness? What do we do when it all starts to feel like too much?
Keywords: Michelle Obama